Effects of alpha-tocopherol on fracture resistance after endodontic treatment, bleaching and restoration - Keren Cristina Fagundes JORDÃO-BASSO; Milton Carlos KUGA; Andrea Abi Rached DANTAS; Mateus Rodrigues TONETTO; Suellen Nogueira Linhares LIMA; Matheus Coêlho BANDÉCA (Sociedade Brasileira de Pesquisa Odontológica, 2016)
Abstract This study evaluated the effects of 10% alphatocopherol on the fracture resistance of endodontically treated teeth subjected to tooth bleaching with hydrogen peroxide and immediately restored with composite resin. Fifty bovine incisors were selected, including 10 sound teeth that constituted the control group (G1 (C)). The remaining 40 teeth, which were endodontically treated, were divided into four groups (n = 10): G2 (CR), consisting of teeth immediately restored with composite resin; G3 (HP + CR), consisting of teeth subjected to tooth bleaching with 38% hydrogen peroxide and immediately restored with composite resin; G4 (HP + SA + CR), which received treatment similar to that used for G3, but with 10% sodium ascorbate gel applied after the bleaching protocol; and G5 (HP + AT + CR), which was similar to G4 but included 10% alphatocopherol gel as an antioxidant. After 24 h, composite restorations were performed, and teeth were subjected to a fracture resistance test at a speed of 0.5 mm/min in an electromechanical testing machine. The axial force was applied with an angle of incidence of 135° relative to the long axis of the root. Data were subjected to ANOVA and Tukey tests (p = 0.05). G1 exhibited the highest fracture resistance (p < 0.05). No significant differences among the other experimental groups were observed. The 10% sodium ascorbate and 10% alphatocopherol gels did not improve the fracture resistance of endodontically treated teeth subjected to bleaching with 38% hydrogen peroxide.